The Solar Water Heating Managers Experiences of Eskom’s Decision to Terminate the Solar Water Heating Rebate Programme - Pillay, Kerushen (The IIE, 2017)
The current energy crisis in South Africa has created an increased focus on Solar Water Heating (Sessa, 2015). The Eskom Solar Water Heating Rebate Programme helped reduce the energy crisis and intended to develop a robust solar water heating industry in South Africa (Energy Efficient Demand Side Management, 2009). The aim of the study explored the solar water heating manager’s experiences of Eskom’s decision to terminate the Solar Water Heating Rebate Programme (SWH RP) in April 2015. The study employed a qualitative research design and the sample size consisted of 3 individual managers of SWH businesses in the Durban area (Du Plooy-Cilliers et al., 2014).The data collection method followed an in-depth interview (Du Plooy-Cilliers et al., 2014; Maree et al., 2016). Thematic analysis was used to execute the data analysis (Braun and Clarke, 2006). The research methods were suitable in obtaining an understanding of the SWH manager’s experiences. The financial loss experienced on solar water heating businesses was identified as the most significant finding. This research study will contribute the existing body of knowledge of solar water heating and will be of beneficial importance to all plumbing and solar water heating businesses in the Durban area.
Keywords: Solar water heating; Energy crisis